EFFECT OF WEED MANAGEMENT PRACTICES ON YIELD OF EFFECT OF WEED MANAGEMENT PRACTICES ON YIELD OF MUNGBEAN ( MUNGBEAN (Vigna radiata igna radiata L.) AND ITS CARRY OVER EFFECT ON SUCCEEDING CHICKPEA ( SUCCEEDING CHICKPEA (Cicer arietinun L.) - VERMA, LATA; KUSHWAHA, H. S. (The Bioscan, 2018)
A field experiment was undertaken during kharif and rabi season of 2016-2017 at Mahatma Gandhi Chitrakoot Gramodaya Vishwavidyalaya, Chitrakoot, Satna (M.P.) to find out the effect of different weed management practices in yield of mungbean and its carry over effect on succeeding chickpea. In mungbean crop, weed control efficiency was noted significantly maximum under manual weeding twice (84%) followed by Pendimethalin 30 EC + Imazethapyr 2 EC at 30 DAS (69 %). While, seed (531 kg/ha) and stover yield (2699 kg/ha) of mungbean were recorded significantly superior under Clodinafop propargyl 8% + Aciflourfen sodium 16.5% @ 187.5 g/ ha at 15-20 DAS. Grain yield of chickpea was obtained significantly superior (774 kg/ha) under residual effect of Pendimethalin 30 EC + Imazethapyr 2 EC @ 0.75 kg/ha followed by Imazamox 35 WG + Imazethapyr 35 WG @ 40 g/ha (772 kg/ha) while, straw yield (2039 kg/ha) was noted higher in Imazamox 35 WG + Imazethapyr 35 WG @ 40 g/ha.